Accurately specifying storm‐time ULF wave radial diffusion in the radiation belts. Issue 14 (23rd July 2015) - Dimitrakoudis, Stavros; Mann, Ian R.; Balasis, Georgios; Papadimitriou, Constantinos; Anastasiadis, Anastasios; Daglis, Ioannis A.
Abstract: Ultralow frequency (ULF) waves can contribute to the transport, acceleration, and loss of electrons in the radiation belts through inward and outward diffusion. However, the most appropriate parameters to use to specify the ULF wave diffusion rates are unknown. Empirical representations of diffusion coefficients often use Kp ; however, specifications using ULF wave power offer an improved physics‐based approach. We use 11 years of ground‐based magnetometer array measurements to statistically parameterize the ULF wave power with Kp, solar wind speed, solar wind dynamic pressure, and Dst . We find that Kp is the best single parameter to specify the statistical ULF wave power driving radial diffusion. Significantly, remarkable high energy tails exist in the ULF wave power distributions when expressed as a function of Dst . Two‐parameter ULF wave power specifications using Dst as well as Kp provide a better statistical representation of storm‐time radial diffusion than any single variable alone. Key Points: We find the best specification for ULF wave radial diffusion in Van Allen Belts Storm‐time ULF waves have a stronger Kp dependence than solar cycle average Proposed new two parameter Kp‐Dst wave specification has huge modeling impacts